Il Libano tra crisi economica, distruzione e speranze di rivoluzione (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
Lebanon is going through an unprecedented economic, social and political crisis. The economy has collapsed, local currency lost 80% of its value and the government defaulted on the debt in March 2020. Meanwhile, mass protests have been challenging the political class that controls the country since the end of the civil war. After a description of the current state of the country, the article analyses the causes of the economic and political crisis, focusing specifically on the clientelism and corruption of the sectarian leaders and on the neo-liberal economic policies implemented in the aftermath of the civil war. Lastly, it analyses the alternative movements that have defied the sectarian system of power throughout the last decades, focusing in particular on the Thawra, a movement that started in October 2019.
Keywords: Lebanon; economic crisis; politics; religion; sectarianism; revolution; protests; Beirut; anti-establishment movements